Etiological Spectrum of Diseases Among the Patients Presenting with per Rectal Bleeding Attending at Surgery Outpatient Department in a Tertiary Level Hospital (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Per rectal bleeding is a problem that is frequently encountered by doctors. There is marked geographical variation in the frequency of different etiologies. This study was conducted to determine the frequency of various causes of per rectal bleeding in patients attending in a tertiary level hospital in Chittagong, Bangladesh.Materials and methods : It was a retrospective study, and non-probability purposive sampling was done. All the patients over ten years of age presenting at the Surgery Outpatient Department with the complain of per rectal bleeding were included. A total of 685 patients were included in this study over a period of 2 years.Results: Mean age of the patients was 36 ± 13 (Mean ± SD) with a range of 10-82 years. Male-female ratio was 1.5:1. Haemorrhoids were the most common cause (34.6%) of per rectal bleeding, followed by chronic anal fissure (26.1%), chronic anal fissure with haemorrhoids (14.9%), colorectal polyps (11.4%) colorectal cancer (8.3%) and Inflammatory Bowel Diseases (IBD) (0.9%). No cause of per rectal bleeding was found in 3.8% of patients. Maximum patients with colorectal cancer presented in their fifth and sixth decades of life.  Conclusion: Haemorrhoids and fissures in ano are the most common causes of per rectal bleeding in our setting. However, the number of colorectal polyps and colorectal cancers are not negligible.JCMCTA 2022 ; 33 (1) : 9-14